2001
DOI: 10.1108/09544780110366105
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge: the key to organisational survival

Abstract: 2009),"Effect of service provider's communication style on customer satisfaction in professional services setting: the moderating role of criticality and service nature"If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In further research, we believe that it would be reasonable to extend TAM with the influential factors of organizational orientation, specifically with the multidimensional variables that we have formed in the present study. Since aCRM IS uses extensive databases of statistical data on customers, the increasing need for the knowledge of statistical tools and methods is expected (Raeside and Walker, 2001). We believe that when analysing the analytical tools of an aCRM IS, the knowledge and skills of the statistical tools should be considered and TAM should be expanded to also include this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…In further research, we believe that it would be reasonable to extend TAM with the influential factors of organizational orientation, specifically with the multidimensional variables that we have formed in the present study. Since aCRM IS uses extensive databases of statistical data on customers, the increasing need for the knowledge of statistical tools and methods is expected (Raeside and Walker, 2001). We believe that when analysing the analytical tools of an aCRM IS, the knowledge and skills of the statistical tools should be considered and TAM should be expanded to also include this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…The awareness of Nigerian telecommunication organizations of the importance of knowledge as a strategic resource for competitive advantage is well exemplified in the findings from this study. Their affirmation of knowledge as the main resource in achieving productivity and competitive advantage is in line with the findings of other similar studies (Choi and Lee, ; Bontis, , ; Raeside and Walker, ). Moreover, the overwhelming acknowledgement of the sampled telecommunications organizations of the need to appoint a chief knowledge officer (CKO) is in agreement with the findings of Bontis ().…”
Section: Discussionmentioning
confidence: 99%
“…Although much has been written about knowledge, knowledge sharing and informal networks in organisations (Raeside and Waker 2001;Swart and Kinnie 2003;Vorakulpipat and Rezgui 2008), little attention has been paid in the literature to the potential impact of downsizing and restructuring on organisational knowledge or knowledge sharing in this context. Since previous research reports poor outcomes from downsizing and restructuring strategies (Cascio 2002;Lee and Corbett 2006), the current study sought to identify whether the consistently reported issues and poor results are associated with the effect downsizing and restructuring may have on knowledge sharing and organisational knowledge.…”
Section: Knowledge Sharingmentioning
confidence: 99%